Samuel Taylor Coleridge, the critical heritage - Jackson, J. R. de J. (James Robert de Jager) (Critical heritage series., 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.